An improved test for shear fracture. (15th October 2016) - Li, D.Y.; Chen, Z.; Sun, L.; Lee, J.W.; Wagoner, R.H.
Abstract: Shear fracture can occur when sheet metal is drawn over a tight die radius during forming. Draw-bend fracture (DBF) tests replicate many aspects of the applied forming situation, but not the high strain rates and plane-strain states typical of industrial conditions. In order to improve on the DBF test, a new high-speed, wide, draw-bend fracture (WDBF) test was configured, implemented, and applied to 5 advanced high strength steels (AHSS) with known constitutive behavior and DBF ductility: DP780, DP590, DP980, TRIP780 and TWIP. Finite element (FE) simulations of the WDBF tests were compared with experiments. Similar comparative simulations were carried out for true plane-strain conditions (unattained experimentally) and for standard DBF tests. The WDBF test was found to be better at reproducing industrial conditions than the DBF test over a much wider range of conditions, but even the new configuration remains substantially different from a hypothetical true plane-strain test. The simulations reveal quantitative assessments of the roles of friction, thermo-mechanical deformation and yield surface choice on shear fracture.